Bioaccumulation of Nickel Ions by Rhizopus delemar - Unsal Açıkel; Gülşah Başkan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The current research investigated the bioaccumulation of Ni(II) ions by Rhizopus delemar in molasses-containing fluids in a batch reactor. Due to the low pH requirements that R. delemar requires, it may grow in wastewater, which has an acidic pH. In the absence of Ni(II) ions, the influence of pH and molasses concentration on the growth rate and concentration of R. delemar were examined. The highest level of microbial growth occurred at a pH of 4.0. Up to 20 g/L of sucrose content increased the maximum R. delemar concentration and the specific growth rate. While the substrate content in each growing medium including molasses was kept constant at 10 g/L, initial concentrations of metal ions were changed between 50 and 250 mg/L to evaluate the bioaccumulation of Ni(II) ions. It was discovered that when metal ions existed, the rate of microorganism growth slowed down as the metal ion concentration increased. The maximum growth rates were discovered to be 0.257 h-1 in the presence of 50 mg/L Ni(II). When media containing 50 mg/L Ni(II) ions, the efficiency of Ni(II) bioaccumulation was found to be 51.8%.